Gambaran Pengetahuan tentang Penyakit Tuberkulosis Paru pada Keluarga Penderita di Puskesmas X - Achmad Cesario Ludiana; Yuliana Ratna Wati (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. This research is aimed to know about the general knowledge of pulmonary tuberculosis in the families of this patients at X Community Health Center, Bandung District. This research uses descriptive method with purposive sampling techniques. The subjects of this research are the families of pulmonary tuberculosis patients at X Community Health Center, Bandung District. The data were obtained using questionnaires. The families of the patients, whom were studied, are 66 subjects consists of 54,4% men, 33,3% with high school level of education, 63,6% with low economic status, 74,2% are Sundanese, 74,2% are workers, 34,8% aged between 46 to 55 years old, and the relation between the families and the patients is 88,89% parents. The pulmonary TB patients’ families’ level of knowledge regarding the signs & symptoms (74,2%), the prevention (77,3%), and the treatment (56,1%) is good. The level of knowledge regarding the mode of transmission (43,9%), Drug-Taking Supervisor (48,5%), and the complication (48,5%) is sufficient. The level of knowledge regarding the causes (39,4%) is low. In general, the pulmonary TB patients’ families’ level of knowledge is sufficient. Abstrak. Penelitian ini bertujuan mengetahui gambaran pengetahuan tentang penyakit tuberkulosis paru pada keluarga penderita TB Paru di Puskesmas X Kabupaten Bandung. Penelitian bersifat deskriptif dengan pendekatan purposive sampling. Subjek penelitian adalah keluarga penderita TB Paru di Puskesmas X Kabupaten Bandung. Data didapatkan menggunakan kuesioner. Keluarga pasien diteliti sebanyak 66 subjek terdiri dari 54,4% laki-laki, 33,3% berpendidikan menengah atas, 63.6% berstatus ekonomi rendah, 74,2% dari suku Sunda, 74,2% responden bekerja, 34,8% berusia antara 46-55 tahun, dan status hubungan keluarga dengan pasien 88.89% adalah orang tua. Tingkat pengetahuan keluarga penderita TB Paru mengenai tanda tanda penyakit TB Paru (74,2%), pencegahan (77,3%), dan pengobatan (56,1%) adalah baik. Tingkat pengetahuan mengenai cara penularan (43,9%), Pengawas Minum Obat (PMO) (48,5%), dan komplikasi (48,5%) adalah cukup. Tingkat pengetahuan mengenai penyebab (39,4%) adalah kurang. Secara umum tingkat pengetahuan keluarga tentang penyakit TB Paru adalah cukup.